2003
DOI: 10.1007/s00406-003-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anxiety disorders and physical illness

Abstract: Anxiety disorders were associated with a specific pattern of cardiac disorders, hypertension, gastrointestinal problems, genitourinary difficulties, and migraine; individuals presenting with anxiety disorders or medical illness need therefore to be evaluated carefully for comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
3
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(160 citation statements)
references
References 18 publications
5
141
3
6
Order By: Relevance
“…A study in South Africa suggested that self-reported diagnosis of hypertension is more common among those with anxiety disorders, depressive disorders and comorbid anxiety-depression compared to those without a mental disorder [10]. Our findings about having controlled blood pressure is harder in the presence of psychological factors and mental disorders such as anxiety and depression were consistent with those of the several studies [11][12][13][14][15]. Rutledge and Hogan reported an overall increased hypertension risk among anxious subjects although the hypertension risk did not reach significance.…”
Section: Discussionsupporting
confidence: 82%
“…A study in South Africa suggested that self-reported diagnosis of hypertension is more common among those with anxiety disorders, depressive disorders and comorbid anxiety-depression compared to those without a mental disorder [10]. Our findings about having controlled blood pressure is harder in the presence of psychological factors and mental disorders such as anxiety and depression were consistent with those of the several studies [11][12][13][14][15]. Rutledge and Hogan reported an overall increased hypertension risk among anxious subjects although the hypertension risk did not reach significance.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, in contrast to controls, heart rate and systolic blood pressure increased significantly in boys with GAD after psychological stress testing (Gerra et al, 2000). Finally, patients with panic or GAD are 5.9 times more likely than controls to have cardiac disorders (angina, myocardial infarction, mitral valve prolapse), even after adjusting for comorbid depression, substance abuse, and gender (Härter, Conway, & Merikangas, 2003).…”
Section: Face Validitymentioning
confidence: 89%
“…Using criteria similar to ours, the Adverse Childhood Experiences (ACE) Study, a CDC supported prospective cohort study of 16,908 adults found a significant relationship between CPL and premature death in adulthood (Brown et al, 2009). Retrospective (e.g., Juang et al, 2004;Kopec and Sayre, 2005) and prospective longitudinal data (Fearon and Hotopf, 2001;Harter et al, 2003;Katerndahl 2008;Jones et al, 2009), link family disruption, physical abuse, separation and maternal loss in early life to chronic physical pain in adulthood. Whether the NL vs. SL probe has a differential effect on pain perception and physiological pain measures, and whether CPL status modifies this interaction should be explored.…”
Section: Panic and Comorbid Conditionsmentioning
confidence: 74%